Association of vitamin E intake in diet and supplements with risk of dementia: A meta-analysis - Zhao, Rangyin; Han, Xiaoyong; Zhang, Hongxia; Liu, Jia; Zhang, Min; Zhao, Weijing; Jiang, Shangrong; Li, Ruilin; Cai, Hui; You, Hong (Frontiers in Aging Neuroscience, 2022)
Background: Dementia is a chronic progressive neurodegenerative disease that can lead to disability and death in humans, but there is still no effective prevention and treatment. Due to the neuroprotective effects of vitamin E, a large number of researchers have explored whether vitamin E can reduce the risk of dementia. Some researchers believe that vitamin E can reduce the risk of dementia, while others hold the opposite conclusion. We therefore performed a meta-analysis to clarify the relationship between them. Methods: We searched the PubMed, Embase, and Web of Science databases for publications with a literature quality of at least 6 points on the connection of dietary and circulating vitamin E with dementia risk. Utilizing lower and higher dosage as contrast, the relative risk (RR) or odds ratio (OR) and 95 percent confidence intervals were derived. The obtained data was shown and assessed using Stata12.0 freeware. Results: We included 20 articles in sum, of which 14 were meal-related and 6 were circulation-related. By comparing the highest intake with the lowest intake or the highest concentration with the lowest concentration, the ORs for extracting high intake or high concentration were as follows: dietary vitamin E (OR = 0.78, 95% CI 0.73 – 0.84 I2 = 43.1%), circulating vitamin E (OR = 0.92, 95% CI 0.88 – 0.96 I2 = 0.0%), and subgroup analysis was conducted by study type, dementia type, diet and supplementation, and serum and plasma. Conclusions: Dietary or vitamin E supplementation can decrease the risk of dementia greatly, and serum vitamin E concentrations are strongly inversely related to the risk of dementia.